Pengaruh Pertumbuhan Penjualan dan Umur Perusahaan Terhadap Penghindaran Pajak Pada Perusahaan Sektor Industri Barang Konsumsi di Bursa Efek Indonesia - Redita Wulandari; Nina Sabrina; Gumulya Sonny Marcel K (Universitas Matana, 2022)
The formulation of the problem in this study is how the influence of sales growth and company age on tax avoidance. The purpose of this study was to examine the effect of sales growth and company age on tax avoidance. The type of research used is associative. There are three variables used, namely sales growth, company age, and tax avoidance. The population in this study is from the annual report of the consumer goods industrial sector companies as many as 54 companies. The sample used was 18 companies which were selected according to the criteria. The data used is secondary. Data collection technique is documentation. The data analysis method in this research is quantitative. The results of this study were assisted by the Statistical Program For Special Science (SPSS). The results show that the effect of sales growth and company age simultaneously has a significant effect on tax avoidance. Partially the effect of sales growth has a significant effect on tax avoidance and the age of the company has no significant effect on tax avoidance in companies in the consumer goods industry sector on the Indonesian Stock Exchange.